SIMILARITIES AND DIFFERENCES IN THE ESSENTIAL OILS OF LAMIACEAE SPECIES - Máthé, I.; Veres, K.; Háznagy-Radnai, E.; Szabó, M. K.; Máthé, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Lamiaceae is an important essential oil bearing family within the Class Dicotyledonopsida. Numerous species, predominantly medicinal plants, belonging to the Subfamily Nepetoideae have relatively high essential oil content, while those with a low or no essential oil content belong to the Subfamily Lamioideae, in Erdtman’s two subfamilial system (1). Recent investigations into the also ‘non volatile oil containing’ species have revealed that all of them contain volatile components, even if only in trace amounts. The goal of the investigations was to contribute to the overview of the essential oil content and composition of several species of the genera Salvia, Stachys, Ballota, Marrubium, Lavandula, Melissa, Ocimum, Hyssopus, etc. of both subfamilies. Experimental plants grown in Central Europe (in Vácrátót, Hungary), were analyzed after steam distillation by GC, GC/MS. The investigations confirmed that all of the species contain some essential oils. Their composition does not significantly differ from the results published by the scientific references, even despite fhe fact that many of the species were grown beyond their natural growing area. Among the more than 100 ingredients found in the essential oils, many, like α-, β-pinen, β-caryophyllene, etc. could be detected in almost all species, while others like α-, β-thujone (Salvia), thymol, carvacrol (Thymus, Satureja, Origanum, etc.), phenylpropane derivatives (Ocimum), etc. were dominant only in certain groups of plants. The results, together with data from the special literature, are evaluated also in view of the recent systematic considerations of the Lamiaceae family. References1. Cantino, P.S., R.W. Sanders, 1982. Subfamilial classification of Labiatae. Systematic Botany, 11. 163-185.Acknowledgement: This work was sponsored by the National Grant (OTKA T43148)